Two new mealybug species from the Falkland Islands (Hemiptera, Sternorrhyncha, Coccoidea, Pseudococcidae) - Williams, D. J. (Zootaxa, 2004)
Two new mealybug species, Rhizoecus bolacis sp. nov. and Trionymus jonesi sp. nov., are described from the Falkland Islands, the first species in any family of scale insects to be recorded from these islands. Both species live on the roots of Bolax gummifera (Apiaceae) and were extracted using Tullgren funnel apparatus.